Seeds of terror an eyewitness account of Al-Qaeda's newest center of operations in Southeast Asia - Ressa, Maria (New York, NY Free Press, a division of Simon & Schuster, Inc., 2003)
An eyewitness account of Al-Qaeda's newest center of operation in Southeat Asia.
Prelude: Face to face with Osama bin Laden -- 1. Pictures don't lie -- 2. The base -- 3. The Asian Osama bin Laden -- 4. Terror HQ -- 5. Black ninjas and jihad in Ambon -- 6. Gangsters in the Philippines -- 7. The new caliphate -- 8. Singapore: Al-Qaeda's Plan A -- 9. Bali: Al-Qaeda's Plan B -- 10. American missteps -- Postlude: "By tongue and teeth."
Includes bibliographical references and index.
Keywords: Qaida (Organization); Terrorism -- Southeast Asia